ANATOMY AND HISTOLOGY OF THE ALIMENTARY CANAL OF ADULT PAPILIO POLYTES POLYTES L. (LEPIDOPTERA: PAPILIONIDAE) - S. M. GAIKWAD; S. R. ALAND; A. B. MAMLAYYA; G. P. BHAWANE (The Bioscan, 2011)
The present study provides the description of the anatomy and histology of the alimentary canal of adult Papilio polytes polytes. The alimentary canal consists of long foregut and hindgut and short midgut. Histologically foregut and hindgut showed outer muscularis, middle folded epithelium and inner chitinous intima. Midgut consists of outer muscularis and inner columnar epithelium and peritrophic membrane surrounding gut content. The epithelium of fore gut and ileum is syncytial and epithelium of colon and rectum is cuboidal. The epithelium of colon shows characteristic six folds. The crop shows well developed spines internally.